Hybrid Ionogel Electrolytes Derived from Polyhedral Oligomeric Silsesquioxane for Lithium Ion Batteries - Lee, Jin Hong; Lee, Albert S.; Lee, Jong-Chan; Hong, Soon Man; Hwang, Seung Sang; Koo, Chong Min (AMER SCIENTIFIC PUBLISHERS, 2017)
Inorganic-organic hybrid ionogels fabricated with 1 M LiTFSI in N-butyl-N-methylpyrrolidinium bis(trifluoromethylsulfonyl) imide (BMPTFSI) crosslinked with a fully methacryl-substituted Polyhedral Oligomeric Silsesquioxane (T8-MMA-POSS) were investigated as gel polymer electrolytes for lithium ion batteries. The effect of T8-MMA-POSS on physical properties of the ionogels was characterized in terms of dimensional stability, ion transport behaviour, and thermal stability. A mere 5 wt% concentration of the cross-linker was able to produce non-flowing hybrid ionogels, leading to high ionic conductivity with good mechanical properties. The lithium battery cell fabricated with ionogels revealed high specific capacity and excellent cycling performance with high Coulombic efficiency at elevated temperature, demonstrating that hybrid ionogels could be a promising candidate electrolyte for use in lithium ion batteries.
Keywords: POLYMER ELECTROLYTES; NANOCOMPOSITES